2022
DOI: 10.1080/13510002.2022.2031516
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of irisin in experimentally induced arthritis: a recent update involving HMGB1/MCP1/Chitotriosidase I–mediated necroptosis

Abstract: Objectives Necroptosis is a tightly adjusted inflammatory necrotizing cell death signaling pathway that participates in pathogenesis of discrete diseases as rheumatoid arthritis (RA). Irisin is a myokine with immuno-modulatory effect. Evaluation of irisin efficiency as a novel therapeutic agent in experimentally induced RA via modulating immuno-inflammatory, necroptotic molecular and biochemical signaling pathways. Methods RA was induced in 30 female Wister albino rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
3
0
0
Order By: Relevance
“…The level of S100A8/A9 was signi cantly higher than that in the non-RA group and the healthy control group, indicating that in the in ammatory joint disease, HMGB1, SII, S100A8/A9 and MCP-1 indeed increased signi cantly, not only in the RA patients. Among them, S100A8 / A9 increased signi cantly in the RA patients (P 0.01), which was similar to the results of Ibrahim-R Raafat et al [23] .…”
Section: Discussionsupporting
confidence: 89%
“…The level of S100A8/A9 was signi cantly higher than that in the non-RA group and the healthy control group, indicating that in the in ammatory joint disease, HMGB1, SII, S100A8/A9 and MCP-1 indeed increased signi cantly, not only in the RA patients. Among them, S100A8 / A9 increased signi cantly in the RA patients (P 0.01), which was similar to the results of Ibrahim-R Raafat et al [23] .…”
Section: Discussionsupporting
confidence: 89%
“…Accumulating documents have recognized necroptosis as a crucial downstream target of the inflammatory process during RA progression, suggesting that necroptosis acts as an important regulator for RA 34,36 . Meanwhile, RIPK3 and MLKL were discovered to be highly expressed in RA patients and have been suggested to be promising therapeutic targets for the treatment of RA 37,38 . As expected, a triggered necroptosis and high levels of RIPK3 and MLKL proteins were discovered in LPS‐mediated C28/I2 cells in this study, while these elevations were greatly inhibited by BIRC2 knockdown, suggesting that BIRC2 knockdown could repress LPS‐caused necroptosis in C28/I2 cells.…”
Section: Discussionsupporting
confidence: 79%
“…34,36 Meanwhile, RIPK3 and MLKL were discovered to be highly expressed in RA patients and have been suggested to be promising therapeutic targets for the treatment of RA. 37,38 As expected, a triggered necroptosis and high levels of RIPK3 and MLKL proteins were discovered in LPS-mediated C28/I2 cells in this study, while these elevations were greatly inhibited by BIRC2 knockdown, suggesting that BIRC2 knockdown could repress LPS-caused necroptosis in C28/I2 cells. In addition, TRADD has been demonstrated to mediate RIPK1-dependent necroptosis by regulating the RIPK3-MLKL pathway, highlighting the critical role of TRADD in regulating necroptosis, 39 which was also reflected in the present study that TRADD overexpression greatly weakened the inhibitory effect of BIRC2 knockdown on necroptosis in LPSmediated C28/I2 cells.…”
Section: Discussionsupporting
confidence: 75%
“…Recent research utilising rats with experimental arthritis showed that irisin has therapeutic potential due to its anti-inflammatory and antioxidant actions [423]. Furthermore, RA patients had substantially reduced irisin levels in their serum when compared to healthy controls [342,349,350], and irisin levels were significantly inversely correlated with disease activity and disability in RA patients [342,349] (Table 5).…”
Section: Irisinmentioning
confidence: 99%